QUANTIFICATION OF ANTI-HBS IMMUNOGLOBULIN IN HEALTH STUDENTS PREVIOUSLY VACCINATED AGAINST HBV - Abrahão Trindade de Lima, Gabriel (2024)
It is estimated that 257 million people worldwide are infected with the hepatitis B virus (HBV). University students in the health field, due to their academic activities and future professions, are in a high-risk group. Vaccination against the virus is considered the most effective prophylactic method, and the state of immunity is characterized by the presence of immunoglobulin against the virus's surface antigen (HBsAg). This study aimed to assess the immunity status of 20 properly vaccinated undergraduate health students through the comparison of qualitative and quantitative methodologies. This study demonstrated that although all students had completed their vaccination schedules, 12 (60%) did not exhibit protective levels of antibodies, and discrepancies between methodologies indicated that rapid tests should not be used as the sole method for establishing a diagnosis